دور المجتمع المدني في التنمية المحلية -  غاليه الياس (Universté ELOUEd-جامعة الوادي, 2022)
الدولة اليوم مطالبة أكثر من أي وقت مضى بضرورة الأخذ بمبادئ المقاربة التشاركية الهادفة الى جعل التدبير المحلي نتاج ارادة تشاركية تنخرط فيها الدولة ومؤسساتها مع مختلف منظمات المجتمع المدني، هذه الأخيرة أصبحت تؤدي دور الحسم في الكثير من القضايا المحورية والمفصلية في المجتمع الذي تعيش فيه، وهي بذلك إما أن تكون أداة تدعم وتؤدي دور السلطة في الدولة من أجل تعزيز مفاهيم الديمقراطية المشاركتية، والحقوق المدنية، والحكم الرشيد، أو أن تلعب الدور العكسي، ذلك أن هذه المؤسسات مشاركتها في تدبير الشأن المحلي مرتبط بمدى استقلاليتها وسبل تفعيلها.The state today is more than ever required to adopt the principles of a participatory approach aimed at making local management the product of a participatory will in which the state and its institutions are involved with various civil society organizations, the latter having become the decisive role in many pivotal and articulated issues in the society in which it lives, which are Thus, it can either be a tool that supports and plays the role of the authority in the state in order to promote the concepts of participatory democracy, civil rights, and good governance, or it can play the opposite role, because these institutions’ participation in managing local affairs is linked to the extent of their independence and ways to activate them.
مذكرة ماستر
Keywords: السلطة في الدولة من أجل تعزيز مفاهيم الديمقراطية المشاركتية; the latter having become the decisive role in many pivotal and articulated issues in the society